Dairy Waste and Potential of Small-Scale Biogas Digester for Rural Energy in India - Prachi Pandey (MDPI AG, 2021)
In order to reduce emissions of greenhouse gases, related global warming and dependency on fossil fuels, it is crucial to promote the uses of renewable energy, and conversion of biomass and organic waste into energy sources. In many parts of the world, a substantial increase in efforts for the conversion of waste into energy is currently being observed. Specifically, biogas technology has been emphasized for the conversion of animal waste into biomethane/biogas because livestock waste is considered to be a substantial source of ambient greenhouse gases, causing climate change. While biogas technology, an anerobic process to convert livestock waste into biogas, is promoted in both developed and developing countries, this review article is focused on improving our existing understanding of small-scale biogas technology and relevance of this technology in rural environment of India. A thorough review research has been performed to gather the information on livestock population, manure production, and potential of biogas technology in India to provide a wholistic information. A summary of the financial supports facilitated by various agencies, the cost of biogas plants, potential uses, and potential challenges in the dissemination of biogas technology in India has been discussed in this study. We anticipate that the data and interpretation provided here will help in understanding the scope of biogas technology in India and will help in formulating the policies which will support the implementation of biogas technologies in developing countries.